Phytoplankton biodiversity and its relationship with aquatic environmental factors in Lake Uvildy, South Urals, Russia (Biodiversitas Journal of Biological Diversity, 2018)
Kostryukova AM, Mashkova V, Krupnova TG, Egorov NO. 2018. Phytoplankton biodiversity and its relationship with aquatic environmental factors in Lake Uvildy, South Urals, Russia. Biodiversitas 19: 1422-1428. Lake Uvildy is one of the largest and the most unique of the South Ural region lakes. This mountain deep lake, which has the status of a natural monument. The purpose of this paper was to study the phytoplankton community structure and the aquatic environmental factors in Lake Uvildy. The phytoplankton samples were collected from 5 sites of Lake Uvildy, then filtered through the plankton net and were preserved in 5% formalin. Species were identi?ed using the handbooks by Sladecek, Yarushina, and Al-Kandari. Water samples were taken for water quality analysis. The several physicochemical parameters were measured in situ by a Portable Meters (Multitest IPL-513 and Multitest KSL-111, Semico Ltd, Russia, Novosibirsk). The others parameters were measured in the laboratory of the Department of Chemistry of the South Ural State University according to the standard methods. The sampling was made during the vegetation period in June-July 2014. The water quality was evaluated using the Shannon biodiversity index. A total of 38 species (11 phyla, 31 genera), including 9 species of Chlorophyta, 13 species of Bacillariophyta, 9 species of Cyanophyta, 4 species of Euglenophyta, 2 species of Chrysophyta, 1 species of Dinophyta, were identified. The phytoplankton species in the lake were mainly represented by Cyanophyta and Bacillariophyta. There were 5 dominant species: Fragilaria crotonensis, Asterionella formosa, Dolichospermum lemmermannii, Microcystis aeruginosa, and Coenococcus planktonicus. The Shannon index value comprised 1.27-2.21. According to the saprobity index values (1.63-2.35), the water in the late is evaluated as satisfactorily clean. Physico-chemical parameters were factors driving the change in phytoplankton community composition in Lake Uvildy.
Keywords: biodiversity; phytoplankton; environmental factors; lake; Shannon index